Ureaplasma urealyticum infection presenting as pyelonephritis and perinephric abscess in an immunocompromised patient. Issue 5 (14th May 2020) - Ngoo, Alexander; Eisemann, Jared; Matsika, Admire; Winkle, David
Abstract : We report a case of an immunosuppressed 67-year-old woman who presented with fever of unknown origin. Further investigation revealed multiple left renal and perinephric abscesses. These were managed with percutaneous drainage and broad-spectrum antibiotics; however, no clinical improvement resulted. No organism was identifiable on standard microscopy and culture of all drain, blood and urine samples taken. Left nephrectomy with right urinary diversion was performed for sepsis management and to protect the patient's right kidney. Eventually, Ureaplasma species' RNA was detected in the patient's drain fluid using PCR and 16S ribosomal RNA gene sequencing. The patient was treated successfully with targeted antibiotic therapy and underwent extensive rehabilitation following this. Histopathology of the nephrectomy specimen suggested xanthogranulomatous pyelonephritis.